PENENTUAN SISTEM PENANGKARAN RUSA TIMOR (Rusa timorensis de Blainville 1822) BERDASARKAN JATAH PEMANENAN DAN UKURAN POPULASI AWAL - Yanto Santosa; Rozza Tri Kwatrina; Agus Priyono Kartono (Media Konservasi, 2012)
Harvest quota and population size could be used to determine deer captive breeding system. Development Center of Deer Captive Breeding Technology at Dramaga Research Forest (DRF) is one of captive breeding projected to be one of professional institution that produce deer offspring for conservation and commercial requirement. The objective of this research was to determine deer captive breeding system harvestbased on harvestharvest quota and initial population size at Dramaga Research Forest. Data and information were collected by literature study and field observation during February until April 2009. The result revealed that based on minimal harvest quota and initial population size, and considering of carrying capacity, semi intensive system (SS) was the best deer captive breeding system alternative for DRF. Keywords: rusa deer, harvest quota, population size, captive breeeding system